Enhancing Students' Technological Literacy Skills through the Wingeom Application in Learning Curved Surface Geometry: A Quantitative Analysis - Suripah, Suripah; Hidayatul Muslim, Rizky (Indonesian Journal of Teaching and Learning, 2025)
This article describes the technological literacy abilities of student using the wingeom application on the material for building curved side rooms at SMPN 37 Pekanbaru. This research uses descriptive research methods with a quantitative approach. The object of this study is the technological literacy ability of students using the Wingeom application, with the subject of research as many as 90 grade IX students of SMPN 37 Pekanbaru. The data from the study were analyzed using SPSS and described the analysis of students' technological literacy skills using the Wingeom application. Based on the results of the study, it shows that most students have the ability to use computers and utilize the internet, be creative in presenting group materials using digital media, the ability to participate in digital spaces, communicate through digital technology media, and understand security when exploring, creating, and collaborating with digital technology after the application of the Wingeom application to the curved side room building material.